No reading allowed : the worst read-aloud book ever; a confusing collection of hilarious homonyms and sound-alike sentences - Haldar, Raj; Carpenter, Chris; Gladfelter, Bryce (Naperville, IL : Sourcebooks eXplore, an imprint of Sourcebooks Kids, 2020)
You can't believe everything you hear! Did you know that a single word can have many different meanings? Sometimes two words that sound alike can be spelled completely differently! Ptolemy the Pterodactyl is back to show us all how absurd and fun language can be when homophones, homonyms, and tricky punctuation are at play.
"A confusing collection of hilarious homonyms and sound-alike sentences."
Ages 4 and up.
Keywords: English language -- Homonyms -- Juvenile literature; English language -- Pronunciation -- Juvenile literature; English language -- Phonetics -- Juvenile literature; English language -- Punctuation -- Juvenile literature; English language -- Orthography and spelling -- Juvenile literature; Homonyms -- Juvenile literature